1976
DOI: 10.1139/y76-021
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 and cyclic AMP in the coronary vasodilatation due to cardiac hyperactivity

Abstract: In the isolated perfused rat heart, the dose-related cardiostimulation produced by norepinephrine (NE) or calcium chloride (Ca2+) was followed by a corresponding increase in coronary flow (CF) and in the cardiac level of adenosine 3',5'-cyclic phosphate (cAMP). Prolonged prostaglandin E2 (pge2) infusion did not change the basic force of contraction, CF, or cAMP level but when NE or Ca2+ were administered, only the responses of the CF and the cAMP were diminished. A phosphodiesterase inhibitor, diazoxide (Dx), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…During this period, the coronary flow normalized if a vasodilator effect of AA had appeared, and the MCD responses remained unchanged. A similar picture was obtained for PGE2 administration, confirming results of our previous studies (Sunahara & Talesnik, 1974;Sen et al, 1976). The slowness of AA in producing blockade of MCD may be ascribed to the buLild-Lip of a suitable intramyocardial cell concentration that would activate the prostaglandin-synthetase and induce the StLbsequent production of prostaglandins; the intracellular increase of prostaglandins would inhibit the adenylate cyclase activation induced by cardiostimulating agents (Sen et al, 1977).…”
Section: Effect Of Non-steroidal Anti-inflammatory Agents On the Reacsupporting
confidence: 88%
See 4 more Smart Citations
“…During this period, the coronary flow normalized if a vasodilator effect of AA had appeared, and the MCD responses remained unchanged. A similar picture was obtained for PGE2 administration, confirming results of our previous studies (Sunahara & Talesnik, 1974;Sen et al, 1976). The slowness of AA in producing blockade of MCD may be ascribed to the buLild-Lip of a suitable intramyocardial cell concentration that would activate the prostaglandin-synthetase and induce the StLbsequent production of prostaglandins; the intracellular increase of prostaglandins would inhibit the adenylate cyclase activation induced by cardiostimulating agents (Sen et al, 1977).…”
Section: Effect Of Non-steroidal Anti-inflammatory Agents On the Reacsupporting
confidence: 88%
“…In the present experiments, we administered AA in the perfusate and found that it stimulated the production of endogenous PGL. The subsequent coronary reactions to cardiostimulation or to hypoxia quite closely resembled the changes obtained when exogenous PGE2 was administered under similar experimental conditions (Sen et al, 1976).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations